(untitled) (Journal of the College of Languages (JCL), 2008)
The comparative literature is a branch of literary criticism which Point to the literary association and relation connecting a mong different world nations and the effect of a nations literature and Culture on another nations literature and culture .So the comparative literature is an image and affront of influence on another nation and countrys literature and culure, for example, the effect of Arabic literature on the Persian , French , English Turkish, Indian and Chinese literature and vice aversa . The current research includes three sections .The first section refers to the meaning and definition of the term “comparative literature ’’, its origin and beginning s. While the second section focuses on the beginning of the comparative literature in the world, especially Europe. Finally , the third section addresses the comparative literature in the Persian contemporary literature whether in poetry , prose, story , play or narration with reference to the influence extent of western authors and poets on the authors and poets of Persian contemporary literature including famous names in the West influencing the poets of Persian contemporary literature .